Association of Child Abuse and Systemic Lupus Erythematosus in Black Women During Adulthood. Issue 6 (3rd June 2021) - Cozier, Yvette C.; Barbhaiya, Medha; Castro-Webb, Nelsy; Conte, Carolyn; Tedeschi, Sara; Leatherwood, Cianna; Costenbader, Karen H.; Rosenberg, Lynn
Abstract : Objective: Exposure to psychosocial stressors may contribute to the onset of systemic lupus erythematosus (SLE) through dysregulation of the adaptive stress response. The present study was undertaken to assess the relationship of childhood physical and sexual abuse to risk of SLE among Black women. Methods: Using data from the Black Women's Health Study, we followed 36, 152 women from 1995 through 2015 with biennial questionnaires. Women reported on exposure to abuse during childhood (up to age 11) in 2005. Self‐reported cases of incident SLE were confirmed as meeting the American College of Rheumatology SLE classification criteria by medical record review. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for SLE among women exposed to physical or sexual abuse during childhood, controlling for potential confounders. Results: We confirmed 101 cases of incident SLE and identified patients who had completed questions on child abuse during 670, 822 person‐years of follow‐up. Both physical and sexual abuse during childhood were associated with statistically significant increases in SLE incidence. The HR for SLE associated with ≥2 episodes of severe sexual abuse compared to no abuse was 2.51 (95% CI 1.29–4.85) after adjustment for alcohol consumption, smoking, body mass index, oral contraceptive use, age at menarche, and parental education. The multivariable‐adjusted HR for SLE with ≥5 episodes of severe physical abuse was 2.37 (95% CI 1.13–4.99). Conclusion: Our results suggest that sexual and physical abuse during childhood increase SLE risk during adulthood among Black women. Research is necessary both to confirm this finding and to understand potential mediating mechanisms.